Informed Family Member Involvement to Improve the Quality of Dementia Care in Nursing Homes. Issue 1 (22nd August 2016) - Tjia, Jennifer; Lemay, Celeste A.; Bonner, Alice; Compher, Christina; Paice, Kelli; Field, Terry; Mazor, Kathleen; Hunnicutt, Jacob N.; Lapane, Kate L.; Gurwitz, Jerry
Abstract : Objectives: To describe the extent to which nursing homes engaged families in antipsychotic initiation decisions in the year before surveyor guidance revisions were implemented. Design: Mixed‐methods study based on semistructured interviews. Setting: U.S. nursing homes (N = 20) from five CMS regions (III, IV, VI, VIII, IX). Participants: Family members of nursing home residents (N = 41). Measurements: Family member responses to closed‐ and open‐ended questions regarding involvement in resident care and antipsychotic initiation. Two researchers used a content analytical approach to code open responses to themes of family involvement in behavior management, decision‐making, knowledge of risks and benefits, and informed consent. Results: Fifty‐four percent of family members felt highly involved in decisions about behavior management. Forty‐two percent recalled being asked how to manage resident behavior without medication, and 17% recalled receipt of information about antipsychotic risks and benefits. Sixty‐six percent felt highly involved in the process of initiating antipsychotic medication; 24% reported being asked for input into the antipsychotic initiation decision and knowing before the antipsychotic was started. Conclusion: Under existing federal regulations but before guidance revisions were implemented in 2013, more than 40% of families reported being involved in nonpharmacological behavior management of family members, but fewer than one in four reported being involved throughout the entire antipsychotic prescribing process. Interventions that standardize family engagement and promote adherence to existing federal regulations are needed. This discussion builds on these findings to weigh the policy options of greater enforcement of existing regulations versus enactment of new legislation to address this challenging issue.